1997
DOI: 10.1901/jeab.1997.67-43
|View full text |Cite
|
Sign up to set email alerts
|

On the Relation Between Preference and Resistance to Change

Abstract: Nevin (1979) noted that preference in concurrent chains and resistance to change in multiple schedules were correlated, in that both measures were affected similarly by variations in parameters of reinforcement such as rate, immediacy, and magnitude. To investigate the relationship between preference and resistance to change directly, we used a within-session procedure that arranged concurrent chains in one half of the session and a multiple schedule in the other half. The same variableinterval schedules serve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

16
131
0
1

Year Published

2000
2000
2018
2018

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 62 publications
(148 citation statements)
references
References 39 publications
16
131
0
1
Order By: Relevance
“…We have measured relative response strength as the difference in log proportion of baseline, log(Bxl/B o 1 ) -log(BjB o2 ) (Grace & Nevin, 1997), plugging in different measures of behavior. Because this measure may be positive or negative (i.e., positive in the case of the richer component's being more resistant to change, but negative for the PREE-type effects in Experiment 2), we can compare the sensitivity of the various measures to differential reinforcement by taking absolute values.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have measured relative response strength as the difference in log proportion of baseline, log(Bxl/B o 1 ) -log(BjB o2 ) (Grace & Nevin, 1997), plugging in different measures of behavior. Because this measure may be positive or negative (i.e., positive in the case of the richer component's being more resistant to change, but negative for the PREE-type effects in Experiment 2), we can compare the sensitivity of the various measures to differential reinforcement by taking absolute values.…”
Section: Discussionmentioning
confidence: 99%
“…Spetch and Dunn (1987) studied pigeons' preference in concurrent chains for FI schedules that provided reinforcement on either 100% or 33% of the trials and found strong preference for the 100% schedule as long as the no-food trials on the 33% alternative were not differentially signaled. Because reinforcement parameters generally have the same effects on preference and resistance to change (Grace & Nevin, 1997), we expected responding in the rich component to be more resistant to change, again with the possible exception of extinction because the generalization decrement during test for the rich component was greater.…”
Section: Methodsmentioning
confidence: 99%
“…The momentum analysis has been derived and elaborated from work with laboratory animals (e.g., Grace & Nevin, 1997;Nevin, Mandell, & Atak, 1983;Nevin, Tota, Torquato, & Shull, 1990). Three studies with humans have demonstrated momentum effects under laboratory conditions (Cohen, 1996;Dube, Mazzitelli, Lombard, & McIlvane, 2000;Mace et al, 1990; for other applications of the momentum metaphor to human behavior see Mace, 1996;Mace, Lalli, Shea, & Nevin, 1992;Nevin, 1996;Plaud & Gaither, 1996).…”
mentioning
confidence: 99%
“…On the basis of these results, Nevin has proposed behavioral momentum theory, which assumes that resistance to change provides a measure of "behavioral mass," or response strength that is independent of response rate (see Nevin & Grace, 2000, for a review). Grace and Nevin (1997) showed that resistance to change and preference in concurrent chains are correlated, leading Nevin and Grace (2000) to propose that "behavioral mass" and "value" are different labels for the same construct that represents what is learned about the conditions of reinforcement associated with a particular stimulus.…”
mentioning
confidence: 99%